Imaginaries of migration : life stories of Mexican migrants in Germany - López García, Yolanda (Kultur und soziale Praxis., 2021)
How do Mexican migrants in Germany perceive themselves and their lives? Innovatively combining theories of interculturality and social imaginaries, Yolanda López García uses the anthropological method of life stories to investigate the understudied area of Mexican migration to Germany. She discusses areas such as quality of life as a motivation for migration, the role of banal nationalism in imaginaries, the dynamic subjective re-construction of Mexicanness, and the process of (imagined) "Germanisation". Yolanda López García ultimately argues that individuals, as social agents, engage with and construct new emerging imaginaries, which may be viewed as important engines of social change.